Bronze Metallurgy in the Times of the Earliest Cities. New Data on the City I of Mari - Montero Fenollós, Juan-Luis (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
Studying the earliest Near Eastern cities means studying a complex series of economic, social, political, ideological and technological transformations (Liverani 1986: 20-23). Metallurgy was not an isolated technological innovation as it formed part of a complex historical process which transformed the model of the village farming communities of the ancient Near East. From the end of the 4th and especially during the first half of the 3rd millennium BC, metals and associated technology were one of the main factors which contributed to changing the way of living and organization of the Syro-Mesopotamian basin, moving from a village model to a style of urban life. The power and control of the commercial network (through which the new raw material circulated) was vital in strengthening the new cities and their military and socio-political elite. Metalworkers had become specialists who, through their work, were transforming society through their effect on such important sectors such as agriculture, war or trade. For Gordon Childe (1962: 79), the first step which ancient man took, within the framework of the ‘Urban Revolution’ in the Near East, to escape ‘Neolithic barbary’ was the creation of a metallurgical production of bronze.